Criminal Responsibility For Perpetrators of Skimming Crime - Abdur Rohim; Mohammad Roesli; Supolo Setyo Wibowo (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2026)
The purpose of this research isCriminal Responsibility for Perpetrators of Skimming Crimes, a qualitative-descriptive research method that produces analytical descriptive data stated by respondents in writing or verbally as well as real behavior, which is researched and studied as a whole. Basic Results of Judge's Considerations in determining the guilt of the perpetrator of skimming crimes in case Number 11/Pid.Sus/2022/PN. Psr. using Law of the Republic of Indonesia Number 11 of 2008 concerning Information and Electronic Transactions as amended and supplemented by Law of the Republic of Indonesia Number 19 of 2016 concerning amendments to Law of the Republic of Indonesia Number 11 of 2008 concerning Information and Electronic Transactions Article 30 Paragraph 2 (two) Jo. Article 46 Paragraph 2 (two) Jo Article 55 Paragraph 1 point 1 of the Criminal Code, the judge uses legal and non-legal considerations. With his legal considerations.